Minimnya pendidikan di daerah terpencil: Analisis dan solusi - Rahmawati, Kurnia (Maliki Interdisciplinary Journal, 2024)
This article discusses various issues to improve the quality of education, the role of technology in improving access to education in remote areas, and collaboration between institutions. The disadvantages caused by lack of education include challenges to improve the quality of life and the threat of losing access to education for young people. To improve education in remote areas, there are several things that can be done. These include better educational facilities, increased access to digital education and technology, and working with governments to secure funding and resources. All parties must work together and support each other to achieve sustainable education solutions.